2018
DOI: 10.1063/1.5017101
|View full text |Cite
|
Sign up to set email alerts
|

Does an electronic continuum correction improve effective short-range ion-ion interactions in aqueous solution?

Abstract: Non-polarizable force fields for hydrated ions not always accurately describe short-range ion-ion interactions, frequently leading to artificial ion clustering in bulk aqueous solutions. This can be avoided by adjusting the nonbonded anion-cation or cation-water Lennard-Jones parameters. This approach has been successfully applied to different systems, but the parameterization is demanding owing to the necessity of separate investigations of each ion pair. Alternatively, polarization effects may effectively be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…proteins, lipids etc.) which are already routinely parameterized with partial charges to account implicitly for electronic polarization (5,32).…”
Section: It Has Been Suggested Bymentioning
confidence: 99%
See 1 more Smart Citation
“…proteins, lipids etc.) which are already routinely parameterized with partial charges to account implicitly for electronic polarization (5,32).…”
Section: It Has Been Suggested Bymentioning
confidence: 99%
“…Neglecting polarizability therefore has consequences for accurately modelling the properties of polarizable anions where many key effects of these ions arise from their electronic responses. For example, the use of NP force fields can lead to inaccuracies in describing short-range ion-water and ion-ion interactions as well as overestimating ion clustering (32,33). Leontyev & Struchebrukhov (34), and expanded upon by Jungwirth et al (26,(35)(36)(37), that the lack of polarization in NP force fields can be compensated for by implicitly accounting for electronic polarization effects through an electronic continuum correction (ECC).…”
Section: Introductionmentioning
confidence: 99%
“…This choice of partial charges, known as Electronic Charge Correction (ECC), was argued to be necessary in a nonpolarizable model to account for the electronic contribution to the dielectric constant. 45,46 ECC has received increased attention in recent years 24,29,[47][48][49] but remains unusual for most ion force fields.…”
Section: Introductionmentioning
confidence: 99%
“…32,43,44 The importance of the ECC model manifests itself for both monovalent and multivalent ions, as they are capable of polarising their surrounding water molecules. 30,[45][46][47][48][49] Mason et al 46 and Pegado et al 50 showed that, predictions of the properties of aqueous salt solutions in the bulk improved significantly using the electronic continuum correction model compared with non-polarisable simulations. However, the applicability of the ECC model has not been fully examined for liquid-liquid and liquid-vapour interfaces.…”
Section: Introductionmentioning
confidence: 99%